Implementasi Algoritma Naive Bayes Terhadap Klasifikasi Jenis Pertanyaan Pada Perancangan Chatbot Untuk Aplikasi Penjualan Songket - Rosa, Adelia; Salamah, Irma; Suroso, Suroso (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Rapid developments in science and technology have had a significant impact on all aspects of people's lives, especially in business. E-commerce has become a popular choice among internet users in Indonesia, including MSMEs. However, conventional sales of songket products still limit product reach and competitiveness. In addition, the sales process generally provides customer service in charge of interacting and serving customer inquiries that can be contacted via telephone number. However, it is considered less effective because the seller has difficulty when responding to various questions from customers, so customers have to wait to get answers regarding the information needed. Therefore, the purpose of this research is to design a chatbot for songket sales applications using the naive bayes algorithm in classifying the types of customer questions, to improve the efficiency and effectiveness of interactions between sellers and customers, and expand the market reach of songket products. This chatbot is designed to simulate interactive conversations and provide sales information to customers quickly and efficiently. The naive bayes algorithm was chosen due to its ease of implementation and high accuracy in text classification. In this study, the chatbot was tested with various types of user questions with 5% of the total 50 questions as testing data. The test results show that the chatbot can classify the type of question with an accuracy of 90% and a precision value of 94%, recall 92%, and F1-Score 92%. In addition, testing of the application system as a whole shows that the application and chatbot are able to provide appropriate and efficient responses to various user questions. With this system, it is hoped that a technology-based solution can be realized that can improve the sales process and customer interaction with sellers, and increase the business potential of traditional songket craftsmen.Â